Examination of alteration and metasomatic zones based on the tectonic setting of the Kamoo region (northeast of Isfahan, Iran) (Nexo Revista Científica, 2020)
Kamoo region (northeast of Isfahan) has an anticline structure with a northwest-southeast trend. The exposed part of this anticline consists of siltstone-sandstone and Jurassic shale, which is located below the Cretaceous formation as an unconformity. Penetration by magmatic masses (dikes) and mineralization events are mainly related to fault systems and fractures in the region and follow the trend of the anticline. In addition, the intensity and variety of alterations are affected by tectonic factors, with alteration and metasomatic haloes having developed next to crushed areas. The alteration process is the main controller of mineral mass grade in the study area; therefore, iron grade in the Kamoo ore has increased by the effects of alteration. The alteration effects include propylitic haloes, iron hydroxides (limonite), and clay mineralization (argillic). The host rock consists of Jurassic shales with siltstone, sandstone, and Cretaceous limestone. Calcareous formations adjacent to granodiorite masses are the main hosts of iron skarns. The results of this study showed that the mineral samples from Kamoo were relatively rich in Light Rare Earth Elements (LREEs); the average La/Yb ratio is about 18.61 and Eu anomaly is between 0.52 and 1.94. Based on the findings of this study, the origin for Kamoo skarn was consistent with the model presented by Meinert, and the region’s mineralization and alteration characteristics correspond to the conditions prevailing in oceanic subduction and back-arc basin environments.